Answer:
x = 2
y = 1
z = 3
Explanation:
Okay, we know y=z-x.
Let's plug in that y-value into the first equation: x + 2 (z - x) -z =1
Simplify that down to x +2z -2x -z = 1
Equation 1 becomes -x + z = 1
Let's plug it into equation 3 and solve to get: 2x - (z - x) +3z = 12
Equation 3 becomes 3x + 2z = 12
Now let's use system of equations for those two equations we just found
3x + 2z = 12
-2x + 2z = 2 ------> multiplied this by 2 to simplify
subtract, and you 5x = 10, x = 2
Use x = 2 and solve for the other variables using the same method (try this on your own!) to get y = 1 and z = 3